Analysis of safeness in a Petri net-based specification of the control part of cyber-physical systems - Wojnakowski, Marcin; Wiśniewski, Remigiusz; Bazydło, Grzegorz; Popławski, Mateusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper proposes an algorithm for safeness verification of a Petri net-based specification of the control part of cyber-physical systems. The method involves a linear algebra technique and is based on the computation of the state machine cover of a Petri net. Contrary to the well-known methods, the presented idea does not require obtaining all sequential components, nor the computation of all reachable states in the system.
Keywords: safeness; control part of the cyber-physical system; Petri nets; state machine cover; place invariant